Associação entre estado nutricional e força de preensão palmar de pacientes internados com diagnóstico de cardiopatia insquêmica pré-intervenção percutânea - Bristot, Vandressa (2015)
Objective: Verify the association between nutritional status and handgrip strength of patients hospitalized with the diagnosis of ischemic heart disease percutaneous pre-intervention. Method: cross-sectional study, with 110 patients with ischemic cardiopathy, hospitalized for percutaneous pre-intervention in the month of July, at a large hospital. For sample characterization, a standardized questionnaire was applied, pre-coded with demographic variables. Ever the assessment of nutritional status was performed through anthropometric measurements of weight, height, the arm circumference, the adductor pollicis, arm muscle circumference, the arm muscle area, arm fat area and body fat, besides the Global Subjective Assessment. The quantification of the handgrip strength of these individuals was assessed by a hand dynamometer. The measures of central tendency and dispersion were calculated for the quantitative variables and for the qualitative variables were presented the absolute frequencies and simple relatives. It was also tested the normality of quantitative variables using the Kolmogorov-Smirnov test. For the association between body mass index and exposure variables the Chi-square test were applied. The student t test was used to verify the difference between the averages of the handgrip strength in individuals with normal body mass index and overweight. Results: 43.6% of cardiopathy were overweight, 52.7% with normal nutritional status and 3.6% with underweight. In the evaluation of nutritional status through the global subjective assessment, 82.7% of the individuals were classified as well nourished. In relation to the body fat, 92.7% were above the average. It was observed that overweight individuals had an average of handgrip strength greater than individuals with normal weight, however without significant differences. In addition, it was not found statistical significances among the variables, nutritional status and handgrip strength. Conclusion: The present study didn´t find association between nutritional status and handgrip strength of patients hospitalized with the diagnosis of ischemic cardiopathy percutaneous pre- intervention. However, it can be observed a high number of overweight individuals and average values of handgrip strength greater than when compared to individuals with normal body mass index